Language Error Analysis on Verified Twitter Timeline - Fajar Kurniadi (Masyarakat Linguistik Indonesia Universitas Andalas, 2017)
Human is a part of language development. Human use language in every aspects of life, including in cyberspace. Cyberspace give a lot of ease in interaction and expressing yourself that sometimes people didn't realize breaking the rules of language use. Twitter is one of social media that provided in cyberspace. Verified twitter account is an account that is consider to have part or influence in the society. The owner of the account can be individual or institution. The objective of this research is to get information about language error in verified twitter account, explain the error and correct it. The research method that used is descriptive analysis. The researcher collect evidences as much as possible and then analyze them. The result of the research is that there are language errors in verified twitter posts, especially in the use of standardized Indonesian language Keyword:Â Error, Language, Twitter, Verified